Functions of the nonsense-mediated mRNA decay pathway in Drosophila development. - Metzstein, M.M.; Krasnow, M.A. (PLoS Genetics, 2006)
Nonsense-mediated mRNA decay (NMD) is a cellular surveillance mechanism that degrades transcripts containing premature translation termination codons, and it also influences expression of certain wild-type transcripts. Although the biochemical mechanisms of NMD have been studied intensively, its developmental functions and importance are less clear. Here, we describe the isolation and characterization of Drosophila "photoshop" mutations, which increase expression of green fluorescent protein and other transgenes. Mapping and molecular analyses show that photoshop mutations are loss-of-function mutations in the Drosophila homologs of NMD genes Upf1, Upf2, and Smg1. We find that Upf1 and Upf2 are broadly active during development, and they are required for NMD as well as for proper expression of dozens of wild-type genes during development and for larval viability. Genetic mosaic analysis shows that Upf1 and Upf2 are required for growth and/or survival of imaginal cell clones, but this defect can be overcome if surrounding wild-type cells are eliminated. By contrast, we find that the PI3K-related kinase Smg1 potentiates but is not required for NMD or for viability, implying that the Upf1 phosphorylation cycle that is required for mammalian and Caenorhabditis elegans NMD has a more limited role during Drosophila development. Finally, we show that the SV40 3' UTR, present in many Drosophila transgenes, targets the transgenes for regulation by the NMD pathway. The results establish that the Drosophila NMD pathway is broadly active and essential for development, and one critical function of the pathway is to endow proliferating imaginal cells with a competitive growth advantage that prevents them from being overtaken by other proliferating cells.